Analisis Keuangan Publik Islam Pada Anggaran Pendapatan dan Belanja Daerah Kabupaten Jember Tahun 2021 - Ezra, Pradipta Imam; Adenan, Moh.; Fatah, Abdul (IJABAH, 2025)
This study aims to analyze the implementation of the 2021 Regional Revenue and Expenditure Budget (APBD) of Jember Regency from the perspective of Islamic public finance. The approach used is descriptive qualitative, with primary data obtained through interviews with the Regional Financial and Asset Management Agency (BPKAD), the Regional Development Planning Agency (Bappeda), and academics, while secondary data is sourced from APBD documents and related literature. The results of the study show that in terms of revenue, Jember Regency is still highly dependent on transfer revenues from the central government, which account for 74% of total regional revenue, while the contribution of Regional Original Revenue (PAD) is relatively small. From an Islamic public finance perspective, this condition shows that the management of local economic potential in accordance with the principle of al-maliyah al-'ammah is not yet optimal. In terms of expenditure, the largest allocation is focused on personnel expenditure, while expenditure for the poor and public welfare is still low. This is not in line with the principle put forward by Ibn Taymiyyah, that state expenditure should prioritize the welfare of the poor and public needs. Thus, the application of the principles of justice, trustworthiness, and welfare in Islamic public finance in Jember Regency still needs to be strengthened.